Anharmonicity of acoustic modes in vitreous TeO2 - Benbattouche, N.; Saunders, George A.; Ab. Aziz, Sidek (Taylor & Francis, 1989)
The temperature dependences between 298 and 358 K of the third-order elastic constants of vitreous TeO2 have been determined from measurements of hydrostatic and uniaxial pressure dependences of ultrasonic wave velocities. The results show that the vibrational anharmonicity of the long-wavelength acoustic modes in this glass is almost independent of temperature in this range. To examine further the effect of anharmonicity of these modes, the second-order elastic constants have been measured down to 4·2 K. A linear dependence found for C11 and C44 between about 80 and 358 K is consistent with the anharmonic contribution causing the temperature dependence of elastic properties in the usual way. Below 80 K, C11 and C44 exhibit anomalous increases whose behaviour and magnitudes are consistent with a contribution from relaxation interactions with two-level systems to the elastic properties of vitreous TeO2 similar to those found in other glasses.